Trade and SDG 13: Action on climate change - Andrew Prag (Asian Development Bank Institute (ADBI), 2017)
This paper assesses the interaction of international trade with climate policies, and the influence of trade on the implementation of SDG 13 (climate change). Although international trade contributes directly to GHG emissions, increased trade can help to achieve development goals in a GHG-efficient manner, provided that GHG emissions are correctly priced everywhere. Given that emissions are not universally priced, the paper examines where policies related to trade may be misaligned with or otherwise hindering climate change objectives. While concluding that the multilateral agreements of the World Trade Organization do not generally prevent governments from pursuing strong domestic climate policy, the chapter does identify potential misalignments. These include import tariffs on environmental goods, barriers to trade in services and domestic policies designed to support local low-carbon industry but which are restrictive of international trade and therefore potentially counter-productive. The paper concludes by stressing the importance of building up resilience in the global trade system in the face of increasingly frequent and severe weather-related shocks.
Keywords: F18; Q54; 330; climate change; trade; sustainable development